Anticipation and Medicine edited by Mihai Nadin - Bobrow, Robert (Journal of Scientific Exploration, 2019)
Anticipation is part of everyday life. We make plans, we look at forecasts, we buy insurance. It is also one of the backbones of medical practice. We anticipate which strains of influenza will arrive and concoct a vaccine accordingly (which is still generally less than 50% effective). We perform Pap smears, which can anticipate cancer of the uterine cervix by ten years. Preventive medicine is a medical specialty. The government-commissioned United States Preventive Services Task Force publishes tomes of screening recommendations. “Anticipation and Medicine” is a collection of “the variety of perspectives pursued in medical anticipation research and associated fields”. The book is broken into seven parts, each containing two to six treatises by a spectrum of authors here and abroad which express opinions and are well-referenced; there is no original research although much existing work is cited.